(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The article reveals promising directions for the development of teacher education in Uzbekistan in the context of reforming higher education. The content of specialist training is also structured in accordance with the requirements of systemic, integrative-differentiated approaches, the principles of consistency and continuity of the learning process.